Textual Metafunction in Students’ IELTS Writing Task 2 - Simanjuntak, Winaria (BRIGHT VISION Journal of Language and Education, 2025)
This research is aimed to analyze the textual metafunction in students’ IELTS Writing Task 2 and the factors underlying the way the subjects used themee and rheme in the descriptive text. This study was conducted using a descriptive-qualitative method. The subjects of the research are 10 high school students who pursue Academic IELTS at Batari School. The technique for collecting data was document analysis and interview. The result of this research showed that the students used three types of thematic progression patterns in combination. The analysis of thematic progression and the interview results showed that the reasons underlying the use of theme and rheme in IELTS task 2 writing were a lack of linguistic skill and lack of argumentative knowledge